An investigation into the doctrine of proper purpose - Prest, Colin Berkley (Department of Commercial Law, 2021)
The doctrine of proper purpose relates to the manner in which directors exercise their powers. Its origins are to be found in the fiduciary relationship in which a director stands towards his company and the concomitant duty that this relationship imports, namely, to use his office and to exercise his powers bona fide in the interests of the company. The significance of the doctrine lies in the separation of the duty to act bona fide in the interests of the company, from the duty to exercise a fiduciary power for the purpose for which· it was intended and not for some imp roper motive. f According to the doctrine, the acts of directors may be invalid if they exercise a fiduciary power for an improper motive, despite the fact that they acted on what they bona fide believed to be in the interests of the company. Inherent in the doctrine is the conflict between the exercise by directors of their managerial powers in terms of the memorandum and articles of association of the company, and the right of the majority of the shareholders to pursue whatever policy they choose 11i thin the company's power, together with the prohibition which rests on either party to usurp the rights of the other. This thesis will address the circumstances leading up to the establishment of the doctrine, and the attitude of the Courts to the doctrine. In this regard there will be an examination of the nature of the office of the director and the obligation which rests upon the directors in the discharge of their fiduciary duties; the nature and development of the doctrine of proper purpose; reached.